2017
DOI: 10.1155/2017/9427359
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Peripartum Management of Patients with Hypofibrinogenemia Resulted in Two Successful Deliveries

Abstract: Fibrinogen is an essential agent involved in maintaining pregnancy and coagulation. Since inherited fibrinogen disorders introduce greater risks for conditions such as placental abruption and postpartum hemorrhage, careful prenatal and perinatal management is essential for this patient population. We report two cases of successful deliveries in patients with hypofibrinogenemia. Case 1 is of a 26-year-old (gravida 1, para 1) woman. The patient's fibrinogen level increased spontaneously to higher than 300 mg/dL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Pregnancy with congenital hypofibrinogenemia is a rare but a high-risk condition. Currently, only a few reports are available on pregnancy associated with hypofibrinogenemia; since 1961, only 10 cases of this disorder during pregnancy have been described [ 4 – 11 ]. Owing to the rarity of the disease and the absences of randomized controlled studies, management of pregnancy with hypofibrinogenemia is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy with congenital hypofibrinogenemia is a rare but a high-risk condition. Currently, only a few reports are available on pregnancy associated with hypofibrinogenemia; since 1961, only 10 cases of this disorder during pregnancy have been described [ 4 – 11 ]. Owing to the rarity of the disease and the absences of randomized controlled studies, management of pregnancy with hypofibrinogenemia is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study has shown the association between Oligohydramnios and preterm risk [ 37 ]. Also Coagulation disorder (Fibrinogen, L_3255-7) is a known risk factor for preterm delivery [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are more than 100 fibrinogen mutations that have been associated with hypofibrinogenaemia. 7 Hypofibrinogenaemia could be: a) mild (fibrinogen levels > 1 g/L): asymptomatic, excessive bleeding can occur after injuries, surgery or delivery; b) moderate (fibrinogen levels between 0.1-1 g/L): bleedings can be spontaneous or caused by injuries, surgery, or delivery; c) severe (undetectable clot): spontaneous, severe, and even life-threatening bleeding may occur. 8 Dysfibrinogenaemia results in abnormal fibrinogen function.…”
Section: Introductionmentioning
confidence: 99%